Oxygen regulation of microbial communities and chemical compounds in cigar tobacco curing - Yang, Juan; Xue, Fang; Li, Dongliang; Chen, Jiaowen; Shi, Guiyang; Song, Guangfu; Li, Youran (Frontiers in Microbiology, 2024)
Introduction Curing is a critical process that determines the sensory quality of cigars. The impact of oxygen on cigar curing and the mechanisms by which it regulates microbial changes affecting cigar quality are not well understood. Methods In this study, we selected handmade cigars from the same batch and conducted curing experiments in environments with varying oxygen concentrations (equivalent to 0.1%, 6–12, and 15% of atmospheric oxygen concentration). We collected samples over 60 days and analyzed the distribution of microbial communities using high-throughput sequencing. Combined with the analysis of total sugars, proteins, flavor substances, and other chemical compounds, we elucidated how different oxygen concentrations affect the cigar curing process, influence microbial community succession, and ultimately impact cigar quality. Results Our results revealed significant differences in bacterial community composition under different oxygen conditions. Under aerobic conditions, Cyanobacteria were the dominant bacteria, while under oxygen-limited conditions, Staphylococcus and Corynebacterium predominated. As oxygen concentration decreased, so did the richness and diversity of the bacterial community. Conversely, oxygen concentration had a lesser impact on fungi; Aspergillus was the dominant genus in all samples. We also found that Enterococcus showed a positive correlation with aspartic acid, alanine, and 4-aminobutyric acid and a negative correlation with cysteine. Cigars cured at 15% oxygen concentration for 60 days exhibited optimal quality, particularly in terms of flavor richness and sweetness. Discussion These findings suggest that oxygen concentration can alter cigar quality by regulating aerobic and anaerobic microbial community succession. The relationship between specific microbial communities and flavor compounds also provides a theoretical reference for developing artificial control technologies in the cigar curing process.